Heroin or fentanyl: Prevalence of confirmed fentanyl in ED patients with suspected heroin overdose - Siri Shastry; Jonathan Lin; Kim Aldy; Jeffrey Brent; Paul Wax; Alex Krotulski; Sharan Campleman; Shao Li; Alison Meyn; Stephanie Abston; Barry Logan; Alexandra Amaducci; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Background United States drug overdose deaths are being driven by the increasing prevalence of fentanyl, but whether patients are knowingly using fentanyl is unclear. We examined the analytical confirmation of fentanyl in emergency department (ED) patients with documented heroin overdose. Hypothesis We hypothesized that the proportion of fentanyl and fentanyl analogs would be higher than that of confirmed heroin. Methods This is a subgroup analysis from a prospective multicenter consecutive cohort of ED patients age 18+ with opioid overdose presenting to 10 US sites within the Toxicology Investigators Consortium from 2020 to 2021. Toxicology analysis was performed using liquid chromatography quadrupole time‐of‐flight mass spectrometry. De‐identified toxicology results were paired with the clinical database. The primary outcome was the proportion of patients with fentanyl analytes detected in their serum. Results Of 1006 patients screened, 406 were eligible, and of 168 patients who reported that they had taken heroin or had a documented heroin overdose, 88% (n = 147) were in fact found to have fentanyl and/or a fentanyl analog present on serum analysis (p < 0.0001). In contrast, only 46 of the 168 patients with reported or documented heroin overdose (27%) were found to have heroin biomarkers present. Conclusion The prevalence of confirmed fentanyl in ED patients with suspected heroin overdose was extremely high, while the prevalence of heroin was very low. There was a high degree of mismatch between the opioids believed to be the overdose agent versus the actual opioids identified on serum toxicology. Clinicians in the United States should presume that fentanyl is involved in all illicit opioid overdoses and should counsel patients on harm reduction measures.